Hikmah Larangan Mendekati Zina dalam Q.S Surah Al-Isra' Ayat 32 Perspektif Tafsirr Al-Mishbah - Saskia Irhamni; Cece Nurhikmah; Amit Saepul Malik (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2024)
What we see before our eyes and through the screen nowadays makes us very, very worried that the crime of free sex is very likely to happen to some of our family members. Why not, the current phenomenon of free sex and adultery in this country presents fantastic numbers. Initially, it was driven by lust, so that lust took control of oneself and adultery arose. In the past, adultery, which was still taboo to discuss, has now become a topic of discussion that is popular with people, considering it normal and a lawful act to do. This research is library research, namely research whose main object is library research. The primary data source is a book of tafsir entitled Tafsir Al-Mishbah: Message, Impression and Harmony of the Al-Qur'an by M. Quraish Shihab. The interpretation methodology uses the tahlili (analytical) and maudhui' (thematic) interpretation methods. The aims of this research are 1). Knowing Quraish Shihab's interpretation of Q.S Al-Isra' verse 32 in Tafsir Al-Mishbah. 2). Knowing the analysis of the interpretation of Al-Mishbah in Q.S Al-Isra' Verse 32 regarding Zina. 3). Knowing the implementation of education on the prohibition of approaching adultery in the present. Based on research analysis, it can be concluded that 1). Quraish Shihab's interpretation of Q.S Al-Isra' verse 32 focuses only on explaining: First, explaining the prohibition on approaching adultery, namely the prohibition on approaching acts that could lead to adultery by explaining one of the initial factors or causes of adultery, second, explaining the bad effects of adultery. That. Quraish Shihab's interpretation of this verse, the focus of his interpretation is only explaining the factors and impacts, there is no explanation regarding prevention. 2). Analysis of Quraish Sihab's interpretation of Q.S Al-Isra' verse 32 Quraish Shihab uses the theory of munasabah. Quraish Sihab in Tafsir Al-Mishbah summarizes Surah Al-Isra' verse 32 with the verses before and after it, namely Q.S Al-Isra' verses 31 and 33, and also correlates it with 2 methods of scholarly opinion, namely Al-Biqa'i and Sayyid Quthub. The three verses above and the two scholars both discuss the impact of adultery, one of which is murder. 3). There are many educational implementations of the prohibition against adultery from a theoretical perspective today. Here the author explains an educational narrative about the problem of adultery, the focus of the education is: 1). Explain the factors that cause adultery. 2). Explain the bad effects of adultery. 3). Explaining tips to avoid adultery, and finally the ultimate goal of this research, the author explains the wisdom or urgency of the prohibition on approaching adultery.